Undergraduate physiotherapy students' competencies, attitudes and perceptions after integrated educational pathways in evidence-based practice: a mixed methods study. (November 2014) - Bozzolan, M.; Simoni, G.; Balboni, M.; Fiorini, F.; Bombardi, S.; Bertin, N.; Da Roit, M.
Abstract This mixed methods study aimed to explore perceptions/attitudes, to evaluate knowledge/ skills, to investigate clinical behaviours of undergraduate physiotherapy students exposed to a composite education curriculum on evidence-based practice (EBP). Students' knowledge and skills were assessed before and after integrated learning activities, using the Adapted Fresno test, whereas their behaviour in EBP was evaluated by examining their internship documentation. Students' perceptions and attitudes were explored through four focus groups. Sixty-two students agreed to participate in the study. The within group mean differences (A-Fresno test) were 34.2 (95% CI 24.4 to 43.9) in the first year and 35.1 (95% CI 23.2 to 47.1) in the second year; no statistically significant change was observed in the third year. Seventy-six percent of the second year and 88% of the third year students reached the pass score. Internship documentation gave evidence of PICOs and database searches (95–100%), critical appraisal of internal validity (25–75%) but not of external validity (5–15%). The correct application of these items ranged from 30 to 100%. Qualitative analysis of the focus groups indicated students valued EBP, but perceived many barriers, with clinicians being both an obstacle and a model. Key elements for changing students' behaviours seem to be internship environment and possibility of continuous practice and feedback.